Phase behavior and permeability of Alkyl-Methyl-Imidazolium Tricyanomethanide ionic liquids supported in nanoporous membranes - Tzialla, O.; Labropoulos, A.; Panou, A.; Sanopoulou, M.; Kouvelos, E.; Athanasekou, C.; Beltsios, K.; V. Likodimos; P. Falaras; Romanos, G. (Separation and Purification Technology, 2014)
This work presents an investigation of the CO2 and N2 single and mixed gas phase permeability through supported ionic liquid membranes (SILMs) developed on ceramic nanoporous substrates with different pore size (1, 5 and 10 nm). ILs from the 1-alkyl-3-methylimidazolium tricyanomethanide family ([RMIM][TCM], with alkyl group, R: ethyl, butyl or octyl) were used as nanopore modifiers. These ILs exhibit high chemical and thermal stability, low viscosity and enhanced CO2 absorption capacity compared to other imidazolium based ILs. Thermal analysis of the developed SILMs unveiled a drastic liquid-to-solid transition upon confinement of the ILs into the pore channels with a size of 1 nm. The IL crystals formed inside these extremely small cavities possessed considerable thermal stability and underwent thermally induced phase transitions that differed significantly from those occurring in the unconfined bulk IL phase or in the IL phase when entrapped into the larger pore channels. The different physical state of the IL under confinement into the pores of different size resulted to significant variation of the flux properties between the developed SILM membranes. The effect of temperature on the CO2 permeability dependend strongly on the crystal thermal stability and microstructure dictated by the confinement into the nanopores. © 2014 Elsevier B.V. All rights reserved.